Mark Heimermann and Brittany Tullis, eds. Picturing Childhood: Youth in Transnational Comics. Austin: U of Texas P, 2017. - Cristina R Rivera (Studies in 20th & 21st Century Literature, 2017)
Review of Mark Heimermann and Brittany Tullis, eds. Picturing Childhood: Youth in Transnational Comics. Austin: U of Texas P, 2017.
Keywords: Children; childhood studies; gender; race; labor laws; comics